2021
DOI: 10.5937/afmnai38-29283
|View full text |Cite
|
Sign up to set email alerts
|

Postural disorders and muscle power in primary school children

Abstract: The aim of the research was to contribute to better understanding of the correlation between postural disorders and muscle power in primary school children. The sample of respondents consisted of 1,120 children, aged 7 to 12 years (549 boys and 571 girls) from the territory of the municipality of Knjaževac. In the assessment of the spinal column status, the device "Spinal Mouse" (Switzerland) was used, while in the analysis of the status of the feet, the podoscope "Pedic" (Hungary) was used. A handheld dynamom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Previous studies have consistently shown a high prevalence of sagittal plane outliers in this age group, and the current study indicates a trend of increasing percentages of postural outliers compared to prior research [25]. When comparing results from various studies [8,26], it is evident that the ages between 10 and 15 represent a period of intense change in sagittal spinal posture among participants, as corroborated by the findings in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies have consistently shown a high prevalence of sagittal plane outliers in this age group, and the current study indicates a trend of increasing percentages of postural outliers compared to prior research [25]. When comparing results from various studies [8,26], it is evident that the ages between 10 and 15 represent a period of intense change in sagittal spinal posture among participants, as corroborated by the findings in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The second most prevalent outlier is kypholordosis, which is significantly more prevalent among the female participants. Among younger elementary school children, there was a significantly lower prevalence of this postural outlier [8,27] while, among participants who are older than those in the analyzed sample, this postural outlier is also significantly prevalent compared to the remaining sagittal plane outliers of the spine [26]. The results can be accounted for by the biological development primarily of the female participants, who have a more inclined pelvis, but it is also reflected in the transformation of both the internal and external features of femininity in the thoracic region, which are characteristic of this phase of biological development.…”
Section: Discussionmentioning
confidence: 98%
“…Abnormal changes in body posture occur in children in two difficult periods when body posture develops. The first difficult period, which is discussed in this report, affects children aged 6-7 years (Bubanj et al, 2012;Gavela-Pérez et al, 2015). This age is characterized by dynamic and rapid changes in growth.…”
Section: Introductionmentioning
confidence: 89%